2021
DOI: 10.1093/sysbio/syab046
|View full text |Cite
|
Sign up to set email alerts
|

Color Polymorphism is a Driver of Diversification in the Lizard Family Lacertidae

Abstract: Color polymorphism – two or more heritable color phenotypes maintained within a single breeding population – is an extreme type of intra-specific diversity widespread across the tree of life. Color polymorphism is hypothesized to be an engine for speciation, where morph loss or divergence between distinct color morphs within a species results in the rapid evolution of new lineages, and thus, color polymorphic lineages are expected to display elevated diversification rates. Multiple species in the lizard family… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 84 publications
(221 reference statements)
0
43
7
Order By: Relevance
“…Sexually dichromatic and monochromatic clades of ray-finned fish on the whole have similar diversification rates, although diversification rates are elevated in the context of either sexual dimorphism or monomorphism at family levels [11]. In birds and lizards, colour polymorphic clades have higher speciation rates compared to monomorphic clades [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Sexually dichromatic and monochromatic clades of ray-finned fish on the whole have similar diversification rates, although diversification rates are elevated in the context of either sexual dimorphism or monomorphism at family levels [11]. In birds and lizards, colour polymorphic clades have higher speciation rates compared to monomorphic clades [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We also wish to stress a previously neglected inherent difficulty with the detection of the morphic speciation model through comparative methods in empirical datasets. The diversification analyses used by us or by Brock et al (2021) test for differences in diversification rates associated with the presence of polymorphism. Yet, the morphic species model predict that "polymorphic lineages should be ancestral and monomorphic lineages should be derived" (Corl et al 2010b), as morphic speciation generates monomorphic species from polymorphic species.…”
Section: Discussionmentioning
confidence: 99%
“…They found that polymorphic populations were often ancestral, and that populations that lost a morph after colonizing a new environment showed reproductive incompatibilities with the ancestral population and rapid phenotypic changes. At macroevolutionnary scale, two studies found that polymorphism increased speciation rates in birds and in lacertid lizards (Hugall and Stuart-Fox 2012; Brock et al 2021). Taken together, these findings support the hypothesis of increased speciation rates in polymorphic species.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that one of the few consistent physical features differentiating the three Angolan Heliobolus species is their coloration patterns, not only of the adults but also of the juveniles. Although coloration in lacertids has traditionally been disregarded as a good diagnostic character for closely related taxa, especially due to the high prevalence of color polymorphism in the family Lacertidae (see Brock et al 2022) and for the difficulty of objectively differentiating between subtle coloration differences, most recent descriptions of southern African lacertids (all backed by molecular phylogenies) have relied on coloration differences to diagnose the newly described species (Conradie et al 2012;Branch et al 2019b;Childers et al 2021;Parrinha et al 2021). This situation agrees with the results of Brock et al (2022) that color polymorphism can be a driver of speciation.…”
Section: Discussionmentioning
confidence: 99%
“…Although coloration in lacertids has traditionally been disregarded as a good diagnostic character for closely related taxa, especially due to the high prevalence of color polymorphism in the family Lacertidae (see Brock et al 2022) and for the difficulty of objectively differentiating between subtle coloration differences, most recent descriptions of southern African lacertids (all backed by molecular phylogenies) have relied on coloration differences to diagnose the newly described species (Conradie et al 2012;Branch et al 2019b;Childers et al 2021;Parrinha et al 2021). This situation agrees with the results of Brock et al (2022) that color polymorphism can be a driver of speciation. More interestingly in this case is the fact that we report here for the first time a clear and diagnostic difference in the coloration of the juvenile specimens.…”
Section: Discussionmentioning
confidence: 99%